Enhancement of Bioactivities of Rhizome Essential Oil of Alpinia galanga (Greater galangal) Through Nanoemulsification. Issue 3 (4th May 2021) - Singh, Subhashree; Sahoo, Suprava; Sahoo, Bhaskar Chandra; Naik, Brundabana; Dash, Manaswini; Nayak, Sanghamitra; Kar, Basudeba
Abstract: Alpinia galanga is commonly known as 'greater galangal' is extensively present across India and Southeast Asia. The essential oil of this zingiberaceae species has high demand in the global market as it has a practice in flavoring food throughout Southeast Asia. The essential oil is also used in spa and perfumery. Rhizome essential oil of A. galanga (AGEO) possesses the myriad therapeutic potential and has more yield than leaf essential oil. However, there are no studies available on the anti-microbial activity of nano-emulsified essential oil of A. galanga (AGNO). Thus, in this current study, AGNO was formulated via low energy emulsification method by using tween 20 and isopropanol as surfactant and co-surfactant respectively with water as solvent. Characterization and validation of nano emulsified oil were done by Litesizer 500 which showed its size less than 100 nm. AGNO exhibited enhanced antimicrobial activity (MIC) against different microbial pathogens like Staphylococcus aureus, Bacillus subtilis, Enterococcus faecalis, Escherichia coli, Aspergillus niger, and Fusarium oxysporum when compared with control (AGEO). It has been concluded from antimicrobial activity that nano emulsified essential oil possesses the highest inhibitory activity against Staphylococcus aureus (0.2 μl/ml). The antioxidant ability of the AGEO and AGNO was also compared by using DPPH free radical scavenging assay. The nano emulsified essential oil possessed significantly higher antioxidant activity (IC50 -9 μg/ml) as compared to the normal essential oil (IC50 -19 μg/ml). Thus, we conclude that the essential oil-based nanoemulsion of A. galanga can be used as an antioxidant and antimicrobial agent in pharmaceutical industries.